Implementation of AHP and Fuzzy Topsis Methods with Techno Economic Analysis Selection of Appropriate Technology for Waste Management Case Study University of Indonesia - Panji Utomo; Adi Surjosatyo (Publikasi Indonesia, 2024)
The